Cost‐effective and simple flow cytometry quantification of receptor‐mediated autophagy using fluorescent tagging - Mija Marinković; Ana Rožić; Denis Polančec; Ivana Novak (FEBS Open Bio)
Mitophagy, a selective clearance of damaged or superfluous mitochondria via autophagy machinery and lysosomal degradation, is an evolutionarily conserved process essential for various physiological functions, including cellular differentiation and immune responses. Defects in mitophagy are implicated in numerous human diseases, such as neurodegenerative disorders, cancer, and metabolic conditions. Despite significant advancements in mitophagy research over recent decades, novel and robust methodologies are necessary to elucidate its molecular mechanisms comprehensively. In this study, we present a detailed protocol for quantitatively assessing mitophagy through flow cytometry using a mitochondria‐targeted fluorescent mitophagy receptor, GFP‐BNIP3L/NIX. This method offers a rapid alternative to conventional microscopy or immunoblotting techniques for analyzing mitophagy activity. Additionally, this approach can theoretically be adapted to utilize any fluorescent‐tagged selective autophagy receptor, enabling the direct and rapid analysis of various types of receptor‐mediated selective autophagy.